Human Nutrition - Kainoa Fialkowski Revilla, Marie; Titchenal, Alan; Calabrese, Allison; Gibby, Cheryl; Meinke, William; Open Textbook Library (Open Textbook Library, 2018)
This textbook serves as an introduction to nutrition for undergraduate students and is the OER textbook for the FSHN 185 The Science of Human Nutrition course at the University of Hawai'i at Mānoa. The book covers basic concepts in human nutrition, key information about essential nutrients, basic nutritional assessment, and nutrition across the lifespan.
Chapter 1: Basic Concepts in Nutrition -- Chapter 2: The Human Body -- Chapter 3: Water and Electrolytes -- Chapter 4: Carbohydrates -- Chapter 5: Lipids -- Chapter 6: Protein -- Chapter 7: Alcohol -- Chapter 8: Energy -- Chapter 9: Vitamins -- Chapter 10: Major Minerals -- Chapter 11: Trace Minerals -- Chapter 12: Nutrition Applications -- Chapter 13: Lifespan Nutrition From Pregnancy to the Toddler Years -- Chapter 14: Lifespan Nutrition During Childhood and Adolescence -- Chapter 15: Lifespan Nutrition in Adulthood -- Chapter 16: Performance Nutrition -- Chapter 17: Food Safety -- Chapter 18: Nutritional Issues
In English.
Description based on print resource
Keywords: Biology -- Textbooks